Narodziny „żydowskiej archeologii” i nowoczesna interpretacja antycznej sztuki żydowskiej - Maciudzińska-Kamczycka, Magdalena (Studia Europaea Gnesnensia, 2014)
The focus of this paper will be on the Jewish experience with art during the late 19 th and early 20 th centuries when Zionist scholars attempted to promote their own vision of Eretz Israel as the ancestral homeland. Jewish archaeology became an important propaganda tool designed both to generate nationalistic pride and provide scientific argument that Jews had possessed a rich and significant visual culture in the antique period of this “Old-New Land”. This is how the need of promoting Jewish nationalism made archaeology and art a very important aspect of the revival process.